Schistosome specific antibodies in individuals co-infected with malaria in Southwest Nigeria (2012)
A cross-sectional study design in two primary schools in Ibadan and Akure was used to determine the prevalence of urinary schistosomiasis, and the human humoral immune response to schistosome antigens in individuals with malaria co-infection. Urine samples were collected from 163 children, while 112 gave blood samples. Malaria parasitaemia was determined by microscopy after Giernsa staining and schistosomiasis by centrifugation technique. Serum samples were analyzed for antibodies to crude S. mansoni soluble egg, adult worm antigens, and crude S. haematobium egg antigen by ELISA. The sample population consisted of 40% (62/163) infected with schistosomiasis, 31% (50/163) with malaria, and 6% (10/163) co-infected. All the co-infected students had asymptomatic malaria with parasite densities ranging from 200 - 4,420 parasites/ul blood. IgG titres to the various Schistosoma antigens did not vary significantly. However, antibody titres to the soluble egg antigen increased with age of volunteers. Antigen specific isotype distribution showed a higher prevalence of IgG3 and lgG4.